Farms of the future: preparing farmers for a believable climate future - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The CCAFS team in collaboration with research teams from Oxford University and the International Center for Tropical Agriculture (CIAT) and local partners initiated the ‘Farms of the Future’ ﬁeld-based research program in the Indo-Gangetic Plains in 2012. The team used the climate analogue tool in the ‘Farms of the Future’ sites identiﬁ ed by CCAFS. By connecting analogue sites, the research aims to enable farmers to better envision how their site-speciﬁ c agricultural future might look like. It helps them test climate resilient cropping systems and technologies in farmers’ ﬁelds.